1991
DOI: 10.1007/bf02050590
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posterior rectopexy on fecal continence

Abstract: Twenty-three patients with rectal prolapse or intussusception were studied to specifically focus on the effect of posterior rectopexy on fecal continence, anal pressure, and rectal capacity. Before operation, five patients were fully continent (A), 10 were continent for solid stools (B) and eight patients were fully incontinent (C). Group A remained fully continent; continence was regained nine times in group B and in group C, three patients regained full continence, two became continent for solid stools, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 9 publications
5
13
0
2
Order By: Relevance
“…On the other hand, 18 percent of the constipated patients complained of worsening of the symptoms and 18 percent of the patients suffered a new onset of constipation. These results are better than other studies [20,22], which reported more than half of the patients to have postoperative constipation.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…On the other hand, 18 percent of the constipated patients complained of worsening of the symptoms and 18 percent of the patients suffered a new onset of constipation. These results are better than other studies [20,22], which reported more than half of the patients to have postoperative constipation.…”
Section: Discussionsupporting
confidence: 39%
“…Improvement in anal canal resting and squeezing pressures following abdominal repair could explain the restoration of continence [21]. Others suggest that the recovery of continence after operation does not depend on sphincter recovery but on improved anorectal sensation or rectal compliance [6,22,23]. An important functional problem frequently encountered after rectopexy procedures is postoperative constipation.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that this finding correlates with episodes of fecal leakage reported by the patient [36]. Clinical improvement in function after surgery, however, has not been associated with a restoration of rectal adaptation, although the high-pressure prolapse waves (already described) are often eliminated in those patients who regain continence following rectopexy [37][38][39][40]. In these successful cases, it has been postulated that there is a reversal of the normal rectoanal pressure gradient before operation, but the importance of this gradient on continence is controversial [41].…”
Section: Physiology and Function Following Altemeier's Proceduresmentioning
confidence: 60%
“…In einem weiteren Teil der Arbeiten kam es postoperativ nur zu einer Erh6hung des Ruhedrucks [6,9] und nur die wenigsten Autoren berichten sowohl fiber eine Zunahme des Ruhe-wie auch des Kontraktionsdrucks [23,31]. Der Grund ffir diese unterschiedlichen Ergebnisse dfirfte einerseits in der Selektion der Patienten (Vermischung von Rektumprolapsf~illen mit Intussuszeptionpatienten), andererseits in der unterschiedlichen Operationstechnik liegen.…”
Section: Radiologische Ergebnisseunclassified
“…Der Nachteil der Methode liegt in der postoperativen Zunahme der Obstipation, fiber die ca. 30-51% der Patienten klagen [6], und in der m6glichen Infektion des implantierten Materials. Von einigen Autoren wird zur Verhinderung einer Obstipation eine Resektion empfohlen, bei welcher allerdings im Gegensatz zu unserer Technik das Rektum nach der Mobilisation mit nicht resorbierbaren N/ihten am Promontorium fixiert und auf eine Implantation eines Fremdstoffs g/inzlich verzichtet wird [7].…”
unclassified